(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2018)
This paper describes the implementation process of a Quality Management System (QMS) at the Laboratory of Poços de Caldas (LAPOC) in Brazil, aiming for ISO/IEC 17025 accreditation. Due to the governmental nature of the entity, all accreditation efforts had to be undertaken on a particular legal framework – not usually favorable to QMS requirements. As the scope consisted of both chemical and radiation test methods (for which only a few labs are accredited worldwide), this initiative turned into a complex endeavor for the organization. In this sense, critical aspects on the development of a QMS are emphasized. LAPOC’s approach to achieve accreditation focused on the branches of documentation development and method validation/uncertainty estimation, whose challenges are here discussed. Upon the successful conclusion of its quality assurance project, LAPOC became the national pioneer in the field of accredited radiation measurements. This case study may be inspiring to other public institutions that struggle to obtain accreditation of radioanalytical test methods in an environment of low resources availability and restricted manpower.